Eksistensi DPS dalam Memoderasi Pengaruh Pembiayaan, Kinerja Keuangan dan Pengungkapan CSR pada Bank Umum Syariah di Indonesia - Ely Masykuroh (IAIN Ponorogo, 2012)
The research was conducted as motivated by previous research related to Corporate Social Responsibility (CSR). Previous researchfound mixed results seen from factors that influence the level of disclosure of CSR such as size, leverage, profitability (financial performance), board composition and ownership structure. The results of these findings is the space to do the test again to make the development or change in methodology. While the results of related research in Islamic banks are financing gap (lack). To the researchers intend to analyze whether the financial effect on the financial performance of Islamic banks as well as the extent to which the existence of the Syaria Supervisory Board moderating relationship. After that study also examines whether financial performance (profitability) affect the disclosure of CSR by entering the variable composition of the Council to moderate the relationship. Methodology that differentiates it from previous research, the supervisory board who previously used as a moderating variable became an independent variable by using Islamicity Disclosure Index and analysis tool using the Moderation Regression Analysis. The results showed no significant effect of financing, profitability and CSR Disclosure, and the role of DPS was also moderate the influence of the relationship between financing and profitability, but the Board of Commissioners did not moderate the influence of the relationship between profitability and CSR disclosure